The Development of Training Participation Conceptual Framework among Academic Staff: A Qualitative Study based on Training Officers Perception at Malaysian Public Universities - Syah Mokhtar, Ikram; Abdullah, Nor Hazana; Anwer Ismael, Darbaz; Othma, Bestoon; Ali, Raman (International Journal of Psychosocial Rehabilitation, 2019)
Training was created for the purpose of focusing on the improvement of specific work skills. Many organizations are now more likely to emphasize the aspects of training and development as a way to promote the development of workers to achieve a highly skilled workforce. In order to realize that aspiration, staff participation in training programs is essential to achieve the objectives and goals set. In line with these requirements, the study aims to continuously explore the factors that influence the participation of academic staff of the Malaysian public universities in programme training. This study has been using a qualitative method where (7) seven training officers from Universiti Awam Malaysia have been interviewed. The data obtained were analysed using Nvivo10 application. Based on the analysis, four major factors were found to have influenced the participation of academic staff in programme training. It consists of individual factors, training, organization and work factors. It is hoped that the findings of this study will benefit and be used by any stakeholders in enhancing knowledge in the topics studied.